Pathological risk factors in upper urinary tract cancer. Issue 1 (2nd December 2013) - Shimamoto, Tsutomu; Inoue, Keiji; Kamata, Masayuki; Kuno, Takahira; Karashima, Takashi; Shuin, Taro
Abstract: Aims: To evaluate pathological factors for prognosis, intravesical recurrence and distant metastasis of upper urinary tract cancer. Methods: This clinical study included 105 patients with renal pelvic and ureteral cancer who were treated at the Kochi Medical School Hospital between 1982 and 2008. Of these patients, 90 who underwent nephroureterectomy were analyzed for pathological risk factors using uni‐ and multivariate analysis. Results: The mean follow‐up period of the 105 patients was 53 months. The disease‐specific survival rates were 70% and 62% at 3 and 5 years. Twenty‐three patients (23%) developed intravesical recurrence, and the mean and median times to recurrence were 18.8 and 9.2 months, respectively. Seventeen patients (19%) had distant metastasis, and the mean and median times to distant metastasis were 25.2 and 25.3 months, respectively. Multivariate analysis identified the pathological grade as an independent risk factor for prognosis ( P  = 0.031), age (≥67 years) and tumor diameter (≥3 cm) as independent risk factors for intravesical recurrence ( P  = 0.007 and 0.003, respectively), and the pathological grade (G1, 2 vs  G3) and lymphatic invasion as independent risk factors for distant metastasis ( P  = 0.006 and 0.003, respectively). Conclusion: Patients with higher‐grade upper urinary tract cancer show a poor prognosis, and often develop distant metastasis, suggesting the need for careful postoperative follow‐up. Those with lymphatic invasion or tumors of 3 cm or more in diameter frequently develop intravesical recurrence and distant metastasis, respectively, indicating the need for strict follow‐up.